The Influence of Experiential Value on Authentic Happiness through Destination Image - Suryadini, Alika (SABA: Journal of Tourism Research, 2024)
This research aims to determine how the value of tourists' experiences influences authentic happiness and destination image and investigates how destinations participate as mediators. In this research, the independent variable is used Experiential value which consists of 4 dimensions: aesthetics, playfulness, consumer return on investment (CROI), and social value. Destination image as a mediating variable that has 3 dimensions: cognitive image, affective image, unique image, and authentic happiness as an independent variable that includes 3 dimensions: pleasant life, engaged life, and meaningful life. The research used an explanatory survey method with a sample of 302 respondents who had camped at Cozy Land, Green Grass and Tangkal Pinus. Data were analyzed using Structural Equation Modeling (SEM) and Confirmatory Factor Analysis (CFA) to validate the suitability of questionnaire items, model fit and hypotheses used. The research results show that simultaneously there is no significant influence, but partially the value of experience has a significant influence on authentic happiness and destination image. However, destination image does not have a significant effect on authentic happiness, so destination image cannot play a mediating role. Researchers recommend increasing the value of experiences to increase tourists' authentic happiness.